2010
DOI: 10.1016/j.clnu.2010.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Serum antioxidants and inflammation predict red cell distribution width in older women: The Women's Health and Aging Study I

Abstract: Background & Aims Red cell distribution width (RDW), a measure of heterogeneity in the size of circulating erythrocytes, is associated with some chronic diseases and predicts mortality. Although oxidative damage and inflammation have been theorized to affect RDW, the relationships of antioxidants and inflammation with RDW have not been well characterized. The aims were to determine whether total serum carotenoids, α-tocopherol, selenium, protein carbonyls, and interleukin-6 (IL-6) are associated with RDW and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
251
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(262 citation statements)
references
References 32 publications
4
251
1
6
Order By: Relevance
“…Like in the case when a car which gets out of control may cause undesirable conditions, over increased inflammation and oxidative stress in our body leads to undesirable outcomes. As a result of changes, they exerted on erythrocytes; increased inflammation [2,3], oxidative stress [5] and neurohormonal activation [18] lead to different size of erythrocytes to involve in the circulation, namely anisocytosis. Possible contribution of inflammation to anisocytosis results from inhibition of the response production against erythropoietin, impaired iron metabolism, and shortened time of red blood cell survival [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like in the case when a car which gets out of control may cause undesirable conditions, over increased inflammation and oxidative stress in our body leads to undesirable outcomes. As a result of changes, they exerted on erythrocytes; increased inflammation [2,3], oxidative stress [5] and neurohormonal activation [18] lead to different size of erythrocytes to involve in the circulation, namely anisocytosis. Possible contribution of inflammation to anisocytosis results from inhibition of the response production against erythropoietin, impaired iron metabolism, and shortened time of red blood cell survival [19].…”
Section: Discussionmentioning
confidence: 99%
“…RDW which is a measure of the variation in the size of circulating erythrocytes (anisocytosis) has been utilized in differential diagnosis of anemia [1]. In addition, increased levels of RDW are closely associated with inflammation [2][3][4], oxidative stress [5] and are related with poor prognoses in stable and unstable cardiac events [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have reported a correlation between RDW and such inflammatory markers as high-sensitivity C-reactive protein, erythrocyte sedimentation rate, interleukin-6, and tumour necrosis factor a [21,22]. Erythropoiesis in oxidative stress results in large immature erythrocytes present in the circulatory system (which increase RDW) [23,24]. However, owing to their poorer oxygen transportation ability, patients' physiology…”
Section: Conflict Of Interest: None Declaredmentioning
confidence: 99%
“…In line with our study, Lippi et al showed a graduated relationship between RDW and hsCRP (24). Semba et al showed that oxidative stress and inflammation might be associated with RDW increase (25). Recently it has been shown that RDW is an essential marker of chronic inflammation and oxidative stress (26).…”
Section: Discussionmentioning
confidence: 99%